Recent Advances in Traditional Chinese Medicine for Treatment of Podocyte Injury - Yao, Tianwen; Su, Wenxiang; Han, Shisheng; Lu, Yan; Xu, Yanqiu; Chen, Min; Wang, Yi (Frontiers in Pharmacology, 2022)
Podocyte is also called glomerular epithelial cell, which has been considered as the final gatekeeper of glomerular filtration barrier (GFB). As a major contributor to proteinuria, podocyte injury underlies a variety of glomerular diseases and becomes the challenge to patients and their families in general. At present, the therapeutic methods of podocyte injury mainly include angiotensin-converting enzyme inhibitors or angiotensin receptor blockers, steroid and immunosuppressive medications. Nevertheless, the higher cost and side effects seriously disturb patients with podocyte injury. Promisingly, traditional Chinese medicine (TCM) has received an increasing amount of attention from different countries in the treatment of podocyte injury by invigorating spleen and kidney, clearing heat and eliminating dampness, as well enriching qi and activating blood. Therefore, we searched articles published in peer-reviewed English-language journals through Google Scholar, PubMed, Web of Science, and Science Direct. The protective effects of active ingredients, herbs, formulas, acupuncture and moxibustion for treatment of podocyte injury were further summarized and analyzed. Meanwhile, we discussed feasible directions for future development, and analyzed existing deficiencies and shortcomings of TCM on treatment of podocyte injury. In conclusion, this paper shows that TCM treatments can serve as promising auxiliary therapeutic methods for the treatment of podocyte injury.